Improvement of bone repair with l-PRF and bovine bone in calvaria of rats. histometric and immunohistochemical study - do Lago, Eliel Scarpioni (2019)
Objectives: The effect of leucocyte- and platelet-rich fibrin (L-PRF), associated with DBBM (deproteinized bovine bone mineral; Bio-Oss®) was investigated and compared with autogenous bone graft as a standard material for filling bone defects. Material and methods: A defect of 5 mm in diameter was performed in 40 calvaria of rats. The animals were divided into 5 groups and received blood clot (CO), autogenous bone (AUT), DBBM (BIO), L-PRF, or DBBM associated with L-PRF (BIO-LPRF). After 4 and 8 weeks, bone regeneration was assessed by histometric and immunohistochemical analyses. Results: The highest mean percentage of bone formation found at 4 and 8 weeks was observed for the BIO-L-PRF group (54.0% ± 2.8 and 63.6% ± 2.2). The lowest mean percentage at 4 and 8 weeks was observed for the CO group (16.7% ± 2.5 and 20.5% ± 1.0). There was statistical similarity among the AUT, BIO, and L-PRF groups. The expressions OC, RUNX 2, and VEGF showed a favorable aspect in the formation of new bone for BIO-L-PRF. VEGF was the marker with the highest expression because it was related to the initial healing process, promoting the migration and proliferation of endothelial cells in the region of the defect. Even after weeks, VEGF maintained a moderate expression. Conclusions: The association of L-PRF with DBBM improved bone repair when these biomaterials were inserted into the defects of the calvaria of rats. Clinical relevance: This reinforces the good performance of bovine bone and L-PRF as filler materials, especially when associated.